The 25(OH)D3, but Not 1,25(OH)2D3 Levels Are Elevated in IBD Patients Regardless of Vitamin D Supplementation and Do Not Associate with Pain Severity or Frequency - Anna Zielińska; Aleksandra Sobolewska-Włodarczyk; Maria Wiśniewska-Jarosińska; Anita Gąsiorowska; Jakub Fichna; Maciej Sałaga (MDPI AG, 2021)
Due to its immunomodulatory effect, vitamin D has been associated with clinical parameters and outcomes in inflammatory bowel diseases (IBDs) which are chronic conditions of the gastrointestinal tract. Upon synthesis or digestion, vitamin D is metabolized in the liver to form 25(OH)D3, the major circulating metabolite. Further renal hydroxylation generates 1,25(OH)2D3, the most potent metabolite. Our aim was to examine the association between vitamin D levels, and its supplementation and pain intensity in 39 IBD patients and 33 healthy individuals. 25(OH)D3 and 1,25(OH)2D3 serum levels were measured. Each subject filled out visual analog scale (VAS) and Laitinen's pain assessment scales. Laboratory results were obtained, and disease activity was assessed. Linear regression was employed to investigate the correlation between 25(OH)D3, 1,25(OH)2D3 and pain intensity, clinical activity parameters, C-reactive protein, disease duration, and dietary habits. In IBD patients, 25(OH)D3 was increased, whereas 1,25(OH)2D3 was not. Vitamin D3 supplementation did not influence their levels. No correlation was found between pain scores, disease activity, inflammatory status, disease duration or dietary habits and both forms of vitamin D. Elevated 25(OH)D3 and normal 1,25(OH)D3 were found in IBD patients as compared to the controls. We discovered no effect from supplementation and no association between pain severity and vitamin D.